Modulation of aflatoxin B1 cytotoxicity and aflatoxin M1 synthesis by natural antioxidants in a bovine mammary epithelial cell line. (June 2019) - Ghadiri, Shiva; Spalenza, Veronica; Dellafiora, Luca; Badino, Paola; Barbarossa, Andrea; Dall'Asta, Chiara; Nebbia, Carlo; Girolami, Flavia
Abstract: Aflatoxin (AF) B1, a widespread food and feed contaminant, is bioactivated by drug metabolizing enzymes (DME) to cytotoxic and carcinogenic metabolites like AFB1-epoxide and AFM1, a dairy milk contaminant. A number of natural antioxidants have been reported to afford a certain degree of protection against AFB1 (cyto)toxicity. As the mammary gland potentially participates in the generation of AFB1 metabolites, we evaluated the role of selected natural antioxidants (i.e. curcumin, quercetin and resveratrol) in the modulation of AFB1 toxicity and metabolism using a bovine mammary epithelial cell line (BME-UV1). Quercetin and, to a lesser extent, resveratrol and curcumin from Curcuma longa (all at 5 μM) significantly counteracted the AFB1-mediated impairment of cell viability (concentration range: 96–750 nM). Moreover, quercetin was able to significantly reduce the synthesis of AFM1. The quantitative PCR analysis on genes encoding for DME (phase I and II) and antioxidant enzymes showed that AFB1 caused an overall downregulation of the detoxifying systems, and mainly of GSTA1, which mediates the GSH conjugation of the AFB1-epoxide. The negative modulation of GSTA1 was efficiently reversed in the presence of quercetin, which significantly increased GSH levels as well. It is suggested that quercetin exerts its beneficial effects by depressing the bio-transformation of AFB1 and counterbalancing its pro-oxidant effects. Highlights: Protection against AFB1-cytotoxicity afforded by selected natural antioxidants was assessed on BME-UV1 cells. Quercetin significantly reduced AFB1-mediated impairment of cell viability. Quercetin significantly reduced AFM1 synthesis. The beneficial effect of quercetin seems to be related to the counterbalance of AFB1 pro-oxidant effect.